Testability Analysis Approach TADATPG for Deterministic Test Generation - Kulak, E. N.; Kaminska, M. A.; Guz, O. A.; Parfentiy, O. N. (Elektronika ir Elektrotechnika, 2006)
Method of testability analysis of digital circuits for deterministic test is offered. This approach is more suitable in comparison with existent classical methods. It is oriented to combinational and sequential circuits and based on topological analysis in gate level. The strategy of circuit’s modification for improvement of fault coverage is proposed. Ill. 10, bibl. 16 (in English; summaries in English, Russian and Lithuanian).